2000
DOI: 10.1051/forest:2000153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endomycorrhizal development and light regimes on the growth of Dicorynia guianensis Amshoff seedlings

Abstract: -The influence of mycorrhizal infection rate and light environment on growth traits was examined for 50-week-old Dicorynia guianensis Amshoff tree seedlings. The seedlings were grown on two soil substrates (control and inoculated) in shade tunnels under three relative light levels (50%, 14% and 1% of full sunshine). For seedlings growing under 1% of full sunlight no significant differences between control and inoculated plants were observed in plant traits though a high rate of endomycorrhizal infection was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…A number of other studies with dipterocarp species have found that, this is indeed the case, with seedlings grown in the understorey having a lower level of EcM colonisation than those in canopy gaps (Becker 1983;Ingleby et al 1998). It appears that the highest levels of mycorrhizal colonisation occur under the light levels where the greatest growth, and hence carbon fixation, of the host plant is found (Prajadinata and Santoso 1993; Béreau et al 2000). However, many EcM fungi are capable of a certain amount of saprotrophic growth and may not, therefore, be totally reliant upon plant carbohydrates leading to the lack of effect of the light conditions on EcM colonisation in this present study.…”
Section: Seedling Growth Ratesmentioning
confidence: 52%
“…A number of other studies with dipterocarp species have found that, this is indeed the case, with seedlings grown in the understorey having a lower level of EcM colonisation than those in canopy gaps (Becker 1983;Ingleby et al 1998). It appears that the highest levels of mycorrhizal colonisation occur under the light levels where the greatest growth, and hence carbon fixation, of the host plant is found (Prajadinata and Santoso 1993; Béreau et al 2000). However, many EcM fungi are capable of a certain amount of saprotrophic growth and may not, therefore, be totally reliant upon plant carbohydrates leading to the lack of effect of the light conditions on EcM colonisation in this present study.…”
Section: Seedling Growth Ratesmentioning
confidence: 52%
“…However, Johnson (1976) observed no decrease in colonisation when the light demanding species Leptospermum scoparium and Coprosma robusta were heavily shaded. In another glasshouse study, Bereau et al (2000) found high levels of colonisation in heavily shaded seedlings of the tropical forest tree Dicorynia guianensis. There have been few studies that have investigated the mycorrhizal colonisation of field-grown seedlings of the same species in different light environments.…”
Section: Introductionmentioning
confidence: 93%
“…Tropical rainforest tree seedlings are much more likely to succumb to damping-off pathogens in the shade than in light gaps, especially near conspecific mature trees (Augspurger, 1984;Hood et al, 2004), and susceptibility to pathogens is greater for less shade-tolerant species (McCarthy-Neumann & Kobe, 2008). Moreover, seedlings often show reduced AM colonization and are generally less responsive (in terms of growth) to AM colonization at low irradiance (Bereau et al, 2000;Gehring, 2003). AM fungi can even reduce seedling survival and growth of shade-tolerant tropical tree species (McCarthy-Neumann & Kobe, 2008).…”
Section: How Does Low Irradiance Influence Fine Root Defence?mentioning
confidence: 99%